2019
DOI: 10.1021/acsami.9b00133
|View full text |Cite
|
Sign up to set email alerts
|

Surface Structure Dependence of Mechanochemical Etching: Scanning Probe-Based Nanolithography Study on Si(100), Si(110), and Si(111)

Abstract: We employed a scanning probe-based lithography process on single-crystalline Si(100), Si(110), and Si(111) surfaces and studied the effects of crystallographic surface structures on mechanochemical etching of silicon in liquid water. The facet angle and etching rate of the mechanochemical process were different from those of the purely chemical etching process. In liquid water, the shape of the mechanochemically etched nanochannel appeared to be governed by thermodynamics of the etched surface, rather than str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 30 publications
1
17
0
Order By: Relevance
“…[62,63] Likewise, ∆𝑉𝑉 * for wear of a silicon AFM tip ranges from 6.7 Å 3 to 55 Å 3 . [43,46] It has also been shown that ∆𝑉𝑉 * depends on the direction of sliding relative to the crystallographic orientation of the surface being worn, [52,53] and on the molecular structure of the reactant species from which films are grown. [66] For the same molecule, the ∆𝑉𝑉 * also varies depending on the reactivity of the substrate on which the molecule is being sheared.…”
Section: B Interpretations Of the Magnitude Of Activation Volumementioning
confidence: 99%
“…[62,63] Likewise, ∆𝑉𝑉 * for wear of a silicon AFM tip ranges from 6.7 Å 3 to 55 Å 3 . [43,46] It has also been shown that ∆𝑉𝑉 * depends on the direction of sliding relative to the crystallographic orientation of the surface being worn, [52,53] and on the molecular structure of the reactant species from which films are grown. [66] For the same molecule, the ∆𝑉𝑉 * also varies depending on the reactivity of the substrate on which the molecule is being sheared.…”
Section: B Interpretations Of the Magnitude Of Activation Volumementioning
confidence: 99%
“…However, the range of experimentally measured activation volumes can be quite large even for the same material system. For example, for tribochemical wear of silicon tips, the range of activation volumes can be as large as ~6.7-115 Å 3 [9,[11][12][13]. With such a large range, the meaning of "local deformation" becomes obscure, and the simple physical picture of ∆V corresponding approximately to the size of the space occupied by molecular groups involved in the chemical reaction might not be sufficient.…”
Section: Main Textmentioning
confidence: 99%
“…Finally, besides interfacial forces, surface wear caused by frictional shear stress is likely to complicate the dynamics [4,159]. Tribochemical reactions may occur between water molecules and the solid surface when the activation energy of these reactions is reduced by an external mechanical action [5,[160][161][162][163][164][165][166][167]. The structure and surface energy of the adsorbed water layer on dynamically changing tribological interfaces may also play vital roles in the mechanochemistry involved in the material removal phenomenon.…”
Section: Perspectivesmentioning
confidence: 99%